Preparation, Characterization, and Catalytic Activity of Tin (Antimony) Substituted and Lacunar Dawson Phosphotungstomolybdates for Synthesis of Adipic Acid - Mohamed Riad Guerroudj; Leila Dermeche; Lynda Mouheb; Tassadit Mazari; Siham Benadji; Chérifa Rabia (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
Tin (antimony) substituted and lacunar Dawson phosphotungstomolybdates (a1-K10P2W12Mo5ÿO61, a1-K8P2W12Mo5SnO61 and a-Cs4SnP2W12Mo6O62,and a-Cs3SbP2W12Mo6O62) were synthesized and characterized by Fourier Transform Infra Red (FTIR), nuclear magnetic resonance (31P NMR), Visible Ultra Violet (UV-Vis) spectroscopy, and X-ray diffraction (XRD). Their catalytic properties were examined in the oxidation reaction of cyclohexanone at 90 °C and that of cyclohexene at 70 °C to adipic acid (AA), in presence of hydrogen peroxide and in free solvent. The effects of catalyst/substrate molar ratios, hydrogene peroxide flow rate, heteropolysalt composition, and cyclohexanol addition on AA yields were studied. The Cs4SnP2W12Mo6O62 (the most efficient) led to 61 % of AA yield from the cyclohexanone oxidation using a catalyst/substrate molar ratio of 13.3×10-4, H2O2 flow rate of 0.5 mL/h, and a reaction time of 20 h.